Focused acoustic vortex generated by a circular array of planar sector transducers using an acoustic lens, and its application in object manipulation - Zhou, Chenchen; Wang, Qingdong; Pu, Shifu; Li, Yuzhi; Guo, Gepu; Chu, Hongyan; Ma, Qingyu; Tu, Juan; Zhang, Dong (Journal of applied physics, 2020)
For enhanced energy utilization with improved flexibility and capability for object manipulation, a focused acoustic vortex (FAV) is devised by installing a spherical acoustic lens on a circular array of planar sector transducers. Based on the acoustic refraction of a concave spherical acoustic lens, numerical simulations show that an FAV with considerable pressure gain and strengthened acoustic gradient force (AGF) can be produced by the effective concentration of acoustic waves. The performance of rotational object trapping is shown by the axial and radial distributions of the AGF for FAVs of different orders. Elastic objects of nanometer, micrometer, millimeter, and even larger-than-wavelength size can be captured with the trapping radius determined by the topological charge. With the established 16-channel experimental system, FAVs of different orders are verified by their clear pressure circles and phase spirals. The trapping radius and rotation speed of object capture are demonstrated using polyethylene particles of various sizes and FAVs of different orders. The favorable results provide an experimentally applicable method of FAV generation using the simplified circular transducer array to accomplish more accurate, stable, and flexible object manipulations with strengthened AGFs. Also, FAVs could offer an efficient means of high-intensity focused ultrasound therapy to improve the therapeutic effect of tumor treatments by accumulating drug particles, thereby enabling more potential applications in clinical practice.